Transition toward Eco-Efficiency of Two Synthesis Methods for Nano-Enabled Pesticides - Melo, Rafael do Valle [UNESP]; do Espirito Santo Pereira, Anderson [UNESP]; Fraceto, Leonardo Fernandes [UNESP]; de Medeiros, Gerson Araujo [UNESP] (American Chemical Society (ACS), 2023)
Nanoparticle synthesis methodologies have been developed over the last decades for reducing the concentrations of pesticides such as atrazine in the environment. In this work, life cycle assessment (LCA) and economic performance analysis tools were used to evaluate the eco-efficiency transition of two laboratory-scale synthesis processes for polymeric nanoparticles (NPo) containing atrazine (ATZ), namely, a double emulsion process (DEm) and a nanoprecipitation process (NPr). Life cycle inventories for both synthesis processes included the flows of matter and energy at a laboratory scale, complementing information from the Ecoinvent database. LCA used the ReCiPe 2016 methodology with a midpoint (H) to produce NPo + ATZ at a concentration of 1 mg ATZ mL-1 of final solution (functional unit). For both processes, freshwater ecotoxicity stood out among the impact categories evaluated, due to significant electricity consumption. The DEm process had a 61% higher total environmental impact, compared to the NPr process. The total cost of the DEm process per functional unit was 5% higher than that of the NPr process. Therefore, NPr achieved a gain of 54% for the eco-efficiency transition, in relation to DEm, for the production of NPo + ATZ. Two steps influenced this result that only occurred in the DEm process: sonication and the use of dichloromethane. Therefore, eco-efficiency enabled identification of the greener production process and the steps that had greater environmental and economic impacts in two NPo synthesis processes.
Keywords: atrazine; herbicide; life cycle assessment; techno-economic analysis